Financial inclusion and its incidence on the tax non-compliance of peruvian MYPE (natural persons) - Tuesta Bardalez, Segundo Eloy (2021)
Objective: To determine the incidence of the financial inclusion in the tax non-compliance of Peruvian MYPE (natural persons). Method: The analytical-synthetic method was used, along with a quantitative approach and a non-experimental design, in which the main technique considered was the documentary and statistical analysis based on the simple correlation model of the investigative variables in a cross-sectional period from 2010 to 2019. Results: The results determine a direct incidence in the tax non-compliance of Peruvian MYPE (natural persons). Conclusion: The financial inclusion has a direct impact on the tax non-compliance of Peruvian MYPE (natural persons), motivated by the continuous growth of the tax informality gaps in the Peruvian economy, and revealing the misalignment and ineffectiveness of the financial and tax policies implemented to promote the development of MYPE.